2000
DOI: 10.1002/1521-3757(20001002)112:19<3561::aid-ange3561>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of the Formation of Microporous Transition Metal Ion Containing Aluminophosphates under Hydrothermal Conditions

Abstract: One of the greatest challenges of experimentalists working in the field of molecular sieve science is the understanding of the principles that determine how porous crystalline materials are formed starting from a precursor gel under hydrothermal conditions. [1] This is far from easy because hydrothermal crystallizations take place in a closed vessel, where many interactions, equilibria, and chemical processes continuously change with crystallization time. [2] The lack of knowledge about these phenomena means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As an example of the usefulness of the applied method we show data on the crystallization of CoAPO. This system was studied previously by in situ diffuse reflectance spectroscopy and electron spin resonance (Weckhuysen et al, 2000), and more recently by independent in situ XAFS and SAXS/WAXS techniques (Grandjean et al, 2005), but since these results were not obtained during one combined measurement it was difficult to understand exactly how changes in each technique corresponded to each other, so the finer details of the crystallization process could not be understood.…”
Section: Introductionmentioning
confidence: 99%
“…As an example of the usefulness of the applied method we show data on the crystallization of CoAPO. This system was studied previously by in situ diffuse reflectance spectroscopy and electron spin resonance (Weckhuysen et al, 2000), and more recently by independent in situ XAFS and SAXS/WAXS techniques (Grandjean et al, 2005), but since these results were not obtained during one combined measurement it was difficult to understand exactly how changes in each technique corresponded to each other, so the finer details of the crystallization process could not be understood.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Relatively few in situ studies have been reported in which attempts were made to follow the crystallization of practically used aluminophosphate molecular sieves. [4,6,10,11,14,15] Raman spectroscopy is a suitable technique to investigate aqueous solutions as well as solid phases of zeolite synthesis mixtures because of the low Raman scattering cross section of water. We have recently developed an apparatus capable of studying hydrothermal reactions in situ using UV Raman spectroscopy.…”
mentioning
confidence: 99%
“…Aluminophosphates (AlPOs) are widely used as catalysts and molecular sieves in industrial processes [1]. Soluble aluminophosphate species, such as [Al(H 2 O) 4 (OH)(H 2 PO 4 )] + , have been suggested as nutrients for the growth of aluminophosphate molecular sieves [2].…”
Section: Introductionmentioning
confidence: 99%